2018
DOI: 10.1016/j.celrep.2017.12.079
|View full text |Cite
|
Sign up to set email alerts
|

INO80 Chromatin Remodeling Coordinates Metabolic Homeostasis with Cell Division

Abstract: SUMMARY Adaptive survival requires the coordination of nutrient availability with expenditure of cellular resources. For example, in nutrient-limited environments, 50% of all S. cerevisiae genes synchronize and exhibit periodic bursts of expression in coordination with respiration and cell division in the yeast metabolic cycle (YMC). Despite the importance of metabolic and proliferative synchrony, the majority of YMC regulators are currently unknown. Here, we demonstrate that the INO80 chromatin-remodeling com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 73 publications
6
40
0
Order By: Relevance
“…To validate the RNA-seq data, we first compared the expression of TORC1 targets like DIP5 (Dicarboxylic amino acid permease) and GAP1 (General Amino acid permease) in DMSO-and rapamycin-treated spores after 0', 30', 60' and 120' following transfer to nutrient medium. Expression of TORC1-downregulated genes 19 DIP5 and GAP1 was enhanced by rapamycin treatment after 1 hour following transfer of spores to nutrient medium consistent with RNA-Seq data (Supplementary Figure S9).…”
Section: Torc1 Regulates the Glucose-responsive Genes During Spore Gesupporting
confidence: 83%
See 4 more Smart Citations
“…To validate the RNA-seq data, we first compared the expression of TORC1 targets like DIP5 (Dicarboxylic amino acid permease) and GAP1 (General Amino acid permease) in DMSO-and rapamycin-treated spores after 0', 30', 60' and 120' following transfer to nutrient medium. Expression of TORC1-downregulated genes 19 DIP5 and GAP1 was enhanced by rapamycin treatment after 1 hour following transfer of spores to nutrient medium consistent with RNA-Seq data (Supplementary Figure S9).…”
Section: Torc1 Regulates the Glucose-responsive Genes During Spore Gesupporting
confidence: 83%
“…Genes in class VIII (N=804) are not regulated by glucose in wild type but only in pka-as cells and were excluded from further analysis. We compared the remaining list of glucose-responsive genes ( N=2469) with the list of 2426 TORC1 target genes reported in a recent transcriptomic study (14,19). We found that 58 % of glucose-responsive genes (N=1436; upregulated=828 and downregulated =608) were co-regulated by TORC1 ( Figure 3C).…”
Section: Overlap Of Torc1 Targets With the Glucose-response Genesmentioning
confidence: 93%
See 3 more Smart Citations